A method for the production of a spherical composite powder for dispersion strengthening of a coating
Patent Information
- Application Number
- CN202611152527.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0011]该方案仍存在如下缺陷:球磨工序较多,导致复合粉末制备周期较长;未设置造粒工序,粉末内部组分分布不均匀
[0022]The raw metal matrix powder and ceramic filler powder used to prepare dispersion-strengthened spherical composite powder are treated in an alternating magnetic field within the cavity of an eddy current layer device to achieve preliminary mechanical alloying and thorough mixing. Then, the powder is rolled, compacted into fragments and locally fractured. These microcracks increase the defect density of the particle crystal structure, enlarge the active specific surface area, and promote the embedding of ceramic filler particles into the metal matrix through mechanical encapsulation. After deagglomeration, granulation, and vacuum drying, plasma treatment melts the metal matrix, wetting and encapsulating the ceramic filler particles to form composite droplets. These droplets condense to form dense, integrally structured metal-ceramic spherical particles with a larger specific surface area and better flowability. This process improves the adhesion between the coating and the substrate, reduces porosity, and enhances the microhardness and wear resistance of the coating.
Smart Images

Figure CN122913496A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing spherical composite powder for dispersion reinforcement of coatings, specifically a method for preparing spherical composite powder for dispersion reinforcement of wear-resistant coatings, which falls under the category of powder metallurgy technology. Background Technology
[0002] Dispersion-reinforced powders, a key material in powder metallurgy for preparing wear-resistant coatings, have attracted numerous experts to invest in research on related preparation technologies. The paper "Research on the Preparation Process of Spherical W-Y₂O₃ System Dispersion-Reinforced Powders by Arc Discharge Thermal Plasma" by Dorofeev AA, Samokhin AV, Fadeev AA, Sinaisky MA, and Alekseev NV, published in *Progress in Chemistry and Chemical Engineering Technology*, Vol. 38, No. 2, 2024, discloses a method for preparing W-Y₂O₃ system dispersion-reinforced powders. The resulting powder particles are spherical with a particle size of 10-50 μm. The process involves granulating tungsten-based nanopowder containing 1.2 wt.% Y₂O₃, followed by processing in an argon arc thermal plasma stream. Experiments determined the spray-drying nanopowder granulation process conditions and the performance parameters of the W-Y₂O₃ nanoparticle suspension. This method can produce round, uniform, non-porous nanopowder microspheres with good mechanical strength, achieving a yield of up to 85% for microspheres with a particle size less than 60 μm. This paper investigates the effects of process parameters for plasma treatment of nanospheres in thermal plasma flow on the morphology, microstructure, bulk density, and flowability of the finished spherical particles.
[0003] However, the drawback of this scheme is that it does not include a mechanical alloying process in its preparation process, which makes it impossible to achieve a more uniform distribution of components in the finished particles.
[0004] The paper "Preparation of Ti-6Al-4V Spherical Powder by High-Frequency Plasma Combining Mechanical Alloying and Spray Granulation" by Zheng Huahao et al., published in Advanced Powder Technology, 2022, Vol. 3322, pp. 1-8, describes the preparation of Ti-6Al-4V spherical powder using a high-frequency plasma spheroidization process combining mechanical alloying and spray granulation. The particle size distribution, morphology, specific surface area, apparent density, flowability, elemental distribution, and alloying element content of the powder at each stage were investigated. The results show that the obtained spheroidized Ti-6Al-4V alloy powder has a dense microstructure, excellent sphericity (98%), an average particle size of 37.8 μm, a narrow particle size distribution, excellent flowability (33.2 s for 50 g of powder), and an apparent density of 2.53 g / cm³. 3 The powder has a uniform elemental distribution, with the majority of elements meeting the standards for Ti-6Al-4V alloys. Radio frequency (RF) plasma spheroidization technology utilizes high-temperature (approximately 10...)... 4With advantages such as high energy density, no electrode contamination, and controllable atmosphere, K) is a promising process for preparing high-quality spherical powders.
[0005] However, this technical solution still has defects. The resulting powder has insufficient alloying degree, and the powder is easily contaminated by impurities introduced by the grinding media. The structure of the pulverizing equipment used is not optimal.
[0006] The invention patent CN107243640V applied for by Che Xiaozhou et al. discloses a high-efficiency metal-ceramic composite powder for thermal spraying structural parts and its preparation method, the steps of which are as follows:
[0007] 1) Mix 20-40 wt.% TiB2 powder with 60-80 wt.% NiCrCoAlY powder uniformly to obtain NiCrCoAlY-TiB2 mixed powder;
[0008] 2) The NiCrCoAIY-TiB2 mixed powder was mixed with process aids and then loaded into a ball mill. It was wet-milled under an inert atmosphere, and then dried and cooled to obtain the composite powder.
[0009] 3) The composite powder is ball-milled and spheroidized under an inert atmosphere to obtain high-performance metal-ceramic nanocomposite powder.
[0010] The resulting composite powder possesses high-temperature wear resistance, thermal fatigue resistance, corrosion resistance, and high-temperature oxidation resistance, while exhibiting excellent flowability and density, with particle sizes mainly concentrated in the 5-50μm range; the preparation process is simple and convenient to operate.
[0011] The proposed solution still has the following drawbacks: the ball milling process is too extensive, resulting in a long preparation cycle for the composite powder; and the lack of a granulation process leads to uneven distribution of components within the powder.
[0012] To address the problems existing in the prior art, this invention was developed. Summary of the Invention
[0013] The objective of this invention is to provide a method for preparing spherical composite powder for dispersion strengthening of coatings. To achieve the above objective, this invention specifically employs the following steps:
[0014] Step 1, Preliminary Mechanical Alloying: The original metal matrix powder, ceramic filler powder, and ferromagnetic grinding media are loaded into the cavity of the eddy current layer equipment and placed in an alternating magnetic field for processing. During this process, the materials undergo vigorous mixing, and the hard ceramic particles are embedded into the plastic metal matrix, completing the preliminary mechanical alloying and uniform powder mixing;
[0015] Step 2, Powder Rolling: After the preliminary mechanical alloying process in Step 1, the powder mixture is fed into the mill roll gap, which is adjusted to a smaller gap (approximately 10–50 μm), and enters the powder rolling process. The mixture components undergo intense shear deformation, and the powder is simultaneously compacted to form fragments and locally fractures. As a result, the density of defects in the particle crystal structure is increased through microcracks, the active specific surface area is increased, and the mechanical alloying effect between the plastic matrix and the ceramic filler is strengthened. The hard filler particles are embedded in the metal matrix through mechanical encapsulation.
[0016] Step 3, De-agglomeration: After the powder rolling process in Step 2, the resulting fragments are pulverized in a vortex layer device equipped with ferromagnetic abrasive media to de-agglomerate them. Heat is generated by collisions between particles, between particles and the chamber walls, and with the ferromagnetic media; therefore, the equipment's cooling jacket is cooled with water during the pulverization process.
[0017] Step 4, Granulation: After completing the deagglomeration process, add the required amount of plasticizer (approximately 2-4% wt% of the powder weight, such as 2% polyethylene glycol or polyvinyl alcohol solution) to the obtained mixture; then send the mixture into the granulation zone, where spherical particles are initially formed under the action of centrifugal force, aerodynamics and gravity. The particles undergo mechanical compaction and drying during the process of being conveyed to the receiving device.
[0018] Step 5, Vacuum drying: Vacuum drying of powder particles to remove moisture and reduce the porosity of the finished product.
[0019] Step 6, Plasma Spheroidization: The vacuum-dried powder particles enter a low-temperature plasma treatment process. The material undergoes three consecutive stages: the original particles are heated; the metal matrix melts, simultaneously wetting and coating the ceramic filler particles to form composite droplets; subsequently, crystallization occurs in the low-temperature zone of the reactor, generating spherical microparticles, with the spatial distribution of the ceramic phase within the microparticles fixed. The resulting powder is a dense, integrally structured metal-ceramic particle, with non-uniform distribution of components within the particle. The spherical shape of the particles provides a larger specific surface area, which is beneficial for improving the bonding strength with the matrix and substrate.
[0020] Step 7, Sieving, Grading and Packaging: The plasma-spheroidized powder is graded and sieved according to the specified particle size and then packaged.
[0021] The advantages of this invention are:
[0022] The raw metal matrix powder and ceramic filler powder used to prepare dispersion-strengthened spherical composite powder are treated in an alternating magnetic field within the cavity of an eddy current layer device to achieve preliminary mechanical alloying and thorough mixing. Then, the powder is rolled, compacted into fragments and locally fractured. These microcracks increase the defect density of the particle crystal structure, enlarge the active specific surface area, and promote the embedding of ceramic filler particles into the metal matrix through mechanical encapsulation. After deagglomeration, granulation, and vacuum drying, plasma treatment melts the metal matrix, wetting and encapsulating the ceramic filler particles to form composite droplets. These droplets condense to form dense, integrally structured metal-ceramic spherical particles with a larger specific surface area and better flowability. This process improves the adhesion between the coating and the substrate, reduces porosity, and enhances the microhardness and wear resistance of the coating. Attached Figure Description
[0023] Figure 1(a, b): Scanning electron microscope images of the preliminary alloyed powder in step 1 of Example 1;
[0024] Figure 2(a, b): Photographs of the powder forming flake-like powder after rolling in step 2 of Example 1;
[0025] Figure 3(a, b): SEM images of the powder particles after granulation and drying in step 5 of Example 1;
[0026] Figure 4(a, b): Electron scanning electron microscope images of the powder after plasma spheroidization in step 6 of Example 1;
[0027] Appendix Figure 5 The wear-resistant coating prepared in Example 1 was sprayed with dispersion-reinforced spherical composite powder. The wear-resistant coating was then used for 1000 hours. The image is a scanning electron microscope image of the wear-resistant coating.
[0028] Appendix Explanation
[0029] Appendix Table 1: Comparison of physical properties of NiCrAl-TiB2 control samples in each step of Example 1;
[0030] Appendix Table 2: Comparison of physical properties of NiCrAl-(Ti,Cr)B2 control samples in each step of Example 2;
[0031] Appendix Table 3: Comparison of physical properties of Ni60-TiB2 control samples after each major step in Example 3;
[0032] Appendix Table 4: Comparison of physical properties of Ni60-TiB2 control samples after each major step in Example 4;
[0033] Appendix 5: Test results of the wear-resistant protective coating in Example 4. Detailed Implementation
[0034] The present invention will be further described below with reference to specific embodiments:
[0035] Example 1
[0036] A near-spherical dispersion-reinforced composite powder with a nickel-chromium-aluminum (NiCrAl) alloy as the matrix and titanium diboride (TiB2) ceramic as the filler phase was prepared. This powder was then used as a raw material for a spray coating, and the microstructure of the coating surface after use was tested. The process included the following steps:
[0037] 1. Preliminary mechanical alloying: High-energy mixing was carried out in an eddy current layer device, using 42.5% by mass of titanium diboride (TiB2) powder (median particle size D50 = 5-8 micrometers, purity 99.5%) and 57.5% by mass of nickel-chromium-aluminum (NiCrAl) powder (aluminum mass fraction 21%, commercial nickel-based spraying powder NiCrAl-SL, produced by Qinghe County Songli Welding Materials Co., Ltd., fine powder median particle size D50 = 16 micrometers); GCr15 grade steel ferromagnetic abrasive media were selected, and the mass ratio of abrasive media to NiCrAl-TiB2 mixed powder was 1:9; the mixture was placed in an alternating magnetic field for 20 minutes to obtain NiCrAl-TiB2 mixed powder; see Figure 1 (a, b). Due to the high hardness of both alloy powder and ceramic powder, mechanical alloying was not ideal, but it achieved the effect of uniform powder mixing.
[0038] 2. Powder rolling: The NiCrAl-TiB2 mixed powder obtained in step 1 is fed into a rolling mill for rolling, so that titanium diboride is embedded into the nickel-chromium-aluminum metal matrix to the maximum extent. The TiB2 particles act as pressure heads in this process. The roll pressure is 3 tons, the roll gap is 10 micrometers, and the synchronous reverse speed of the rolls is 5 revolutions / minute. See Figure 2 (a, b) for photos of the mixed powder after rolling, forming scaly powder.
[0039] 3. Deagglomeration: The NiCrAl-TiB2 mixed powder after rolling in step 2 is placed in the eddy current layer equipment for further processing. The raw material powder after crushing and rolling is formed into fragmented powder. The processing time is 5 minutes.
[0040] 4. Granulation: Add 4% by mass of polyvinyl alcohol aqueous solution (concentration 2%) as a process aid to the powder obtained in step 3, and granulate using a disc granulator. The particle size of the finished product is controlled between 45 and 120 micrometers. The granulated powder, as shown in Figure 3 (a, b), is mostly an agglomeration of alloy particles and ceramic particles.
[0041] 5. Vacuum drying: Place the composite powder obtained in step 4 into a vacuum drying oven and keep it at 150°C for 3 hours to remove residual moisture. Then cool it to room temperature to obtain dried composite powder.
[0042] 6. Plasma spheroidization: The dried composite powder obtained in step 5 is fed into an radio frequency plasma processing device for spheroidization treatment; the powder is coaxially fed into the plasma flame of the induction plasma torch via a water-cooled probe, and the powder feeding rate is 4-7 kg / h; the plasma working gas is an argon-hydrogen mixture (90% argon and 10% hydrogen), and the carrier gas (argon) flow rate is 5-15 L / min; the scanning electron microscope images of the composite powder particles after plasma spheroidization are shown in Figure 4 (a, b), and most of the powder particles are spherical.
[0043] 7. Sieving, grading and packaging: The metal ceramic powder obtained in step 6 is sieved again to select the target particle size components and then vacuum packaged.
[0044] The powders after plasma spheroidization in steps 3, 4 and 6 were tested. The plasma spheroidization process resulted in increased bulk density, improved flowability, and excellent microhardness.
[0045] Table 1. Comparison of physical properties of NiCrAl-TiB2 control samples after each step
[0046]
[0047] The dispersion-reinforced spherical composite powder prepared in Example 1 was used to prepare an approximately 100 μm wear-resistant coating on DC53 (Daido Special Steel, Japan) using high-velocity oxygen fuel spraying (HVOF). After 1000 hours of use, the surface structure of the wear-resistant coating is detailed in [the image / description]. Figure 5 The composite powder is tightly bonded to the substrate, resulting in a coating with significant wear resistance.
[0048] Example 2
[0049] The preparation of spherical dispersion reinforced composite powder with nickel-chromium-aluminum (NiCrAl) metal as the matrix and titanium-chromium boride ((Ti,Cr)B2) ceramic as the filler phase for use as a sprayed wear-resistant coating specifically includes the following steps:
[0050] 1. Preliminary mechanical alloying: High-energy mixing was carried out in an eddy current layer device, using 43.24% by mass of titanium chromium boride ((Ti,Cr)B2) powder (median particle size D50 = 5-8 μm, purity 99.5%) and 56.76% by mass of nickel chromium aluminum (NiCrAl) powder (aluminum mass fraction 21%; commercial nickel-based spraying powder NiCrAl-SL, manufacturer: Qinghe County Songli Welding Materials Co., Ltd., fine powder median particle size D50 = 16 μm); GCr15 steel ferromagnetic abrasive media were used, with a mass ratio of abrasive media to NiCrAl-(Ti,Cr)B2 mixed powder of 1:9; the mixture was placed in an alternating magnetic field for 15 minutes to obtain NiCrAl-(Ti,Cr)B2 mixed powder.
[0051] 2. Powder rolling: The NiCrAl-(Ti,Cr0B2 mixed powder obtained in step 1 is fed into a rolling mill for rolling, so that (Ti,Cr)B2 is embedded into the nickel-chromium-aluminum metal matrix to the maximum extent; TiB2 powder particles act as pressure heads, the roll pressure is 3 tons, the roll gap is 10μm, and the synchronous reverse rotation speed of the rolls is 5 rpm.
[0052] 3. Deagglomeration: The NiCrAl-(Ti,Cr)B2 mixed powder after rolling in step 2 is fed back into the vortex layer equipment for further processing. The composite raw material after crushing and rolling is formed into scaly fragment powder. The processing time is 5 minutes.
[0053] 4. Granulation: Take the powder obtained in step 3 and granulate it using a disc granulator; add 4% by mass of a 2% polyvinyl alcohol aqueous solution as a process aid to the powder and granulate it using a disc granulator. The finished particle size is 45-120μm.
[0054] 5. Vacuum drying: Place the composite powder obtained in step 4 into a vacuum drying oven and keep it at 150°C for 3 hours to remove residual moisture. Then cool it to room temperature to obtain dried composite powder.
[0055] 6. Plasma spheroidization: The dried composite powder obtained in step 5 is fed into the radio frequency plasma processing equipment for spheroidization. The powder is coaxially transported to the plasma flame of the induction plasma torch via a water-cooled probe. The powder feeding rate is 4-7 kg / h. The plasma working gas is an argon-hydrogen mixture (90% argon and 10% hydrogen), and the carrier gas (argon) flow rate is 5-15 L / min.
[0056] 7. Sieving, grading and packaging: The metal ceramic powder prepared in step 6 is sieved to select the target particle size components and then vacuum packaged.
[0057] Table 2. Comparison of physical properties of NiCrAl-(Ti,Cr)B2 control samples after each step
[0058]
[0059] Example 3
[0060] The preparation of a spherical dispersion reinforced composite powder with nickel (Ni60) metal as the matrix (89.86%) and titanium diboride (TiB2) ceramic (10.14%) as the filler phase for use as a sprayed wear-resistant coating specifically includes the following steps:
[0061] 1. Preliminary mechanical alloying: High-energy mixing treatment is carried out in the eddy current layer equipment. 10.14% by mass of titanium diboride (TiB2) powder (median particle size D50 = 5-6 micrometers, purity 99.5%) and 89.86% by mass of Ni60 spraying powder (commercial spraying powder, produced by Zhujin Technology (Tianjin) Co., Ltd., fine powder median particle size D50 = 25 micrometers) are used. GCr15 steel ferromagnetic abrasive media are used, with a mass ratio of abrasive media to Ni60-TiB2 mixed powder of 1:9. The mixture is placed in an alternating magnetic field for 15 minutes to obtain Ni60-TiB2 mixed powder.
[0062] 2. Powder rolling: The Ni60-TiB2 mixed powder obtained in step 1 is placed in a rolling mill for rolling, so that the titanium diboride is embedded into the Ni60 metal matrix to the maximum extent. The TiB2 particles act as pressure heads in this process. The rolling pressure of the rolls is 5 tons, the roll gap is 50 micrometers, and the synchronous reverse rotation speed of the rolls is 10 revolutions per minute.
[0063] 3. Deagglomeration: The Ni60-TiB2 mixed powder after rolling in step 2 is fed back into the vortex layer equipment for processing. The composite raw material after crushing and rolling is formed into scaly fragment powder. The processing time is 10 minutes.
[0064] 4. Granulation: The powder obtained in step 3 is granulated using a disc granulator. A 4% by mass and 2% concentration of polyvinyl alcohol aqueous solution is added to the powder as a process aid. The finished particles are granulated using a disc granulator, and the particle size is controlled between 45 and 120 micrometers.
[0065] 5. Vacuum drying: Place the composite powder obtained in step 4 into a vacuum drying oven and keep it at 150°C for 3 hours to remove residual moisture. Then cool it to room temperature to obtain dried composite powder.
[0066] 6. Plasma spheroidization: The dried composite powder obtained in step 5 is fed into an RF plasma processing device for spheroidization. The powder is coaxially transported to the plasma flame of the induction plasma torch via a water-cooled probe at a rate of 4-7 kg / h. The plasma working gas is an argon-hydrogen mixture (90% argon and 10% hydrogen), and the carrier gas (argon) flow rate is 5-15 L / min.
[0067] 7. Sieving, grading and packaging: The metal ceramic powder prepared in step 6 is sieved to select the target particle size components and then vacuum packaged.
[0068] Table 3. Comparison of physical properties of Ni60-TiB2 control samples after each major step
[0069]
[0070] Example 4
[0071] The preparation of a spherical dispersion reinforced composite powder with nickel (Ni60) metal as the matrix (65.64%) and titanium diboride (TiB2) ceramic (34.36%) as the filler phase for use as a sprayed wear-resistant coating specifically includes the following steps:
[0072] 1. Preliminary mechanical alloying: High-energy mixing was carried out in an eddy current layer device, taking 34.36% by mass of titanium diboride (TiB2) powder (median particle size D50 = 5-6 μm, purity 99.5%) and 65.64% by mass of Ni60 commercial spraying powder (manufacturer: Zhujin Technology (Tianjin) Co., Ltd., fine powder median particle size D50 = 25 μm); GCr15 steel ferromagnetic abrasive media was selected, and the mass ratio of abrasive media to Ni60-TiB2 mixed powder was 1:9; the mixture was placed in an alternating magnetic field for 15 minutes to obtain Ni60-TiB2 mixed powder.
[0073] 2. Powder rolling: The Ni60-TiB2 mixed powder obtained in step 1 is fed into a rolling mill for rolling, so that titanium diboride is embedded into the Ni60 metal matrix to the maximum extent; TiB2 particles act as pressure heads, the roll pressure is 5 tons, the roll gap is 50μm, and the synchronous reverse rotation speed of the rolls is 15 rpm.
[0074] 3. Deagglomeration: The Ni60-TiB2 mixed powder after rolling in step 2 is placed in the eddy current layer equipment for further processing. The composite raw material powder after crushing and rolling is formed into scaly fragment powder. The processing time is 10 minutes.
[0075] 4. Granulation: Add 4% by mass and 2% concentration of polyvinyl alcohol aqueous solution to the powder obtained in step 3 as a process aid, and granulate using a disc granulator; the particle size of the finished product is controlled between 45 and 120 μm.
[0076] 5. Vacuum drying: Place the composite powder obtained in step 4 into a vacuum drying oven and keep it at 150°C for 3 hours. After evaporating and removing residual moisture, cool it to room temperature to obtain dried composite powder.
[0077] 6. Plasma spheroidization: The dried composite powder obtained in step 5 is spheroidized in an RF plasma processing device; the powder is coaxially transported to the plasma flame of the induction plasma torch via a water-cooled probe at a powder feeding rate of 4-7 kg / h; the plasma working gas is an argon-hydrogen mixture (90% argon and 10% hydrogen), and the carrier gas (argon) flow rate is 5-15 L / min.
[0078] 7. Sieving, grading and packaging: The metal ceramic powder obtained in step 6 is sieved to select the target particle size components and then vacuum packaged.
[0079] Table 4. Comparison of physical properties of Ni60-TiB2 control samples after each major step
[0080]
[0081] As can be seen from Tables 3 and 4, the microhardness of the prepared spherical dispersion-reinforced composite powder increases significantly with the increase of the ceramic phase ratio.
[0082] Using the high-velocity flame spraying (HVOF) process, a spherical dispersion reinforced composite powder with nickel (Ni60) metal as the matrix (65.64%) and titanium diboride (TiB2) ceramic (34.36%) as the filler phase is sprayed onto the steel surface to form a good wear-resistant protective coating. Its performance indicators are detailed in Table 5.
[0083] Table 5. Test results of wear-resistant protective coatings
[0084]
[0085] The analysis results in Table 5 show that the prepared coating has excellent microhardness and relatively low porosity; at the same time, the coating exhibits excellent bonding strength.
[0086] It should be noted that the specific embodiments described above enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the present invention in any way. Therefore, although the embodiments in this specification have described the present invention in detail, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention; and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the present invention patent.
Claims
1. A method for preparing spherical composite powder for dispersion strengthening of coatings, comprising: preliminary mechanical alloying of metal matrix powder and ceramic filler powder, powder rolling, deagglomeration, granulation, vacuum drying, plasma spheroidization, sieving, grading, and packaging, wherein: (1) Preliminary mechanical alloying: The original metal matrix powder, ceramic filler powder and ferromagnetic grinding media are loaded into the cavity of the eddy current layer equipment and placed in an alternating magnetic field for processing. (2) Powder rolling: After completing the preliminary mechanical alloying process in step 1, the powder mixture is fed into the mill roll gap with the roll gap adjusted to 10-50μm and enters the powder rolling process. (3) Deagglomeration: After the powder rolling process in step 2, the resulting fragments are crushed in a vortex layer device equipped with ferromagnetic grinding media. (4) Granulation: After the deagglomeration process in step 3, a 2% wt% polyvinyl alcohol solution with a total powder weight of 4% wt% is added to the mixture, and granulation is carried out using a disc granulator. (5) Vacuum drying: Vacuum drying of the granulated powder particles from step 4; (6) Plasma spheroidization: The powder particles after vacuum drying in step 5 are sent to a radio frequency plasma treatment device for spheroidization treatment. (7) Sieving, grading and packaging: The powder after plasma spheroidization in step 6 is graded and vacuum-packed according to the specified particle size.
Citation Information
Patent Citations
High-performance metal and ceramic composite powder used for feeding of thermal spraying structure and preparation method for high-performance metal and ceramic composite powder
CN107243640A